Auxiliary tool for firing insulator, manufacturing method and using method
By using auxiliary tools with elastic buffer layer and anti-blocking material during the insulator firing process, the problem of cracks on the head after firing with large-size disc-shaped suspended insulators is solved, achieving a more uniform stress and higher product quality.
Patent Information
- Application Number
- CN202411967652.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-11
AI Technical Summary
Large-size disc-shaped suspended insulators are prone to microcracks on the head after firing, resulting in the mechanical strength and electrical insulation performance that cannot meet the requirements, reducing the firing pass rate.
An auxiliary tool for insulator firing is adopted, including a carrier and a buffer pad placed on the carrier. The buffer pad is composed of an elastic buffer layer made of refractory material, embedded with anti-stick material, and a layer of quartz sand is laid on the surface of the buffer layer.
The weight of the firing product is uniformly transferred through the elastic buffer layer, avoiding uneven stress, greatly reducing the generation of microcracks, and improving the quality and pass rate of the product. At the same time, the use of anti-stick materials and quartz sand extends the service life of the buffer pad and reduces adhesion.
Smart Images

Figure CN119594729A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulator production, and in particular to an auxiliary tool for insulator sintering, a manufacturing method and a use method. Background Art
[0002] In the production of insulators, the porcelain parts of the insulators are placed on a kiln cart, and the kiln cart is pushed into the kiln for firing at a temperature of about 1200°C. After firing, the fired products (that is, the fired porcelain parts) are prone to adhesion to the carrier (the kiln cart or a special bowl or shelf on the kiln cart for supporting the porcelain parts).
[0003] To solve the above problem, technicians have proposed a method of brushing anti-sticking material on the carrier on which the porcelain pieces are placed (the anti-sticking material is also called isolation material, and the carrier is an object such as kiln tools, pads, etc. that support the fired products). The anti-sticking layer formed by the anti-sticking material can prevent or reduce the adhesion between the porcelain pieces and the carrier after firing. This method is mentioned in existing patents, such as a special adhesive for electric porcelain rod-shaped firing with patent publication number CN113880556A.
[0004] The current production method has no problem for small-sized porcelain parts or those with low requirements on product performance, but there are problems for large-sized disc-shaped suspension insulators. This is because the porcelain parts of the disc-shaped suspension insulators are in contact with the carrier with their heads facing downward and their umbrellas facing upward during firing. The entire support is subjected to force using the small-sized end of the porcelain part. The larger the outer diameter of the umbrella part of the insulator, the greater the weight, and the greater the pressure on the head of the porcelain part (because in disc-shaped suspension insulators, the increase in the specifications of the insulator often refers to the increase in the outer diameter of the umbrella part, but after the specifications become larger, the head of the insulator generally does not increase or the increase ratio is smaller than the increase ratio of the outer diameter of the umbrella part, so the head of the porcelain part is subjected to great pressure). There are certain small bumps on the surface of the carrier. On the basis of excessive pressure on the head, the head after firing is prone to be deformed due to the small bumps. The presence of bumps and depressions results in uneven force, and the pressure-bearing surface of the head is not air permeable after contact, which makes it easy for microcracks to appear on the head of large-sized disc-shaped suspension porcelain parts after firing. Large-sized disc-shaped porcelain parts are often used in high-voltage transmission lines where high electrical insulation performance and mechanical destructive strength requirements are required, such as disc-shaped suspension insulators that can withstand mechanical destructive loads of 420KN, 550KN, and 800KN (this type of disc-shaped suspension insulator with high mechanical destructive load requirements and large size weighs about 14kg, while the weight of a general small-sized disc-shaped suspension insulator is about 5kg). The appearance of cracks will make the insulator's mechanical strength unable to meet the requirements, and the electrical insulation performance will also fail to meet the requirements, greatly reducing the firing pass rate of large-sized disc-shaped porcelain parts. Summary of the invention
[0005] The present invention aims to provide an auxiliary tool for firing insulators to solve the problem that cracks are easily generated on the head of large-sized disc-shaped suspended porcelain parts after firing.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme:
[0007] An auxiliary tool for insulator sintering comprises a carrier and a buffer pad placed on the carrier, wherein the buffer pad comprises an elastic buffer layer made of refractory material, and the buffer layer is embedded with an anti-sticking material.
[0008] The principle and advantage of this solution are: when this solution is adopted, a large-sized disc-shaped suspended porcelain piece is inverted on an auxiliary tool with its head downward before firing, and the buffer pad on the auxiliary tool directly contacts the fired porcelain piece. In this way, even if the surface of the carrier is uneven, the elastic buffer layer can ensure that the weight of the fired product is evenly transferred to the carrier, thereby ensuring that the porcelain piece of the disc-shaped suspension insulator is evenly stressed during the firing process, greatly reducing or even avoiding the generation of microcracks, and improving the quality and pass rate of the product.
[0009] The refractory material of the buffer layer improves the service life and usage demand of the buffer pad. The anti-sticking material attached to the buffer layer has excellent refractory properties, which helps to improve the refractory properties of the buffer pad. At the same time, the anti-sticking material is embedded in the buffer layer to increase the compressive strength of the buffer layer. Under the heavy pressure of large-size disc suspension insulators, the increase in compressive strength helps the buffer layer not to be easily flattened to the point where it cannot be restored, thereby increasing the service life of the buffer pad. On the other hand, the buffer pad with anti-sticking material can also reduce adhesion to the burned products, thereby further increasing the service life of the buffer pad.
[0010] In addition, when the buffer pad needs to be replaced, the anti-sticking material on the buffer pad makes it difficult for the buffer pad to adhere to the carrier, thereby facilitating the replacement of the buffer pad.
[0011] Preferably, as an improvement, the surface of the buffer layer that contacts the sintered product is paved with a layer of quartz sand.
[0012] Beneficial effects: When this solution is adopted, the quartz sand arranged on the surface of the sintered product has multiple effects:
[0013] First, quartz sand can prevent the fired products (such as the porcelain parts of insulators) from sticking to the buffer layer, playing an isolating role. It can also increase the service life of the buffer pad through the high fire resistance of quartz sand. In the test, the service life of the buffer pad without quartz sand is only half of that of the buffer pad with a layer of quartz sand.
[0014] Secondly, the quartz sand not only makes the buffer pad play a cushioning role for the fired product, but also utilizes the gaps between the sands to form a porous structure, which helps to improve the quality of the contact parts of the fired product, making the difference between the contact parts and other parts when heated smaller.
[0015] Third, the anti-sticking material is attached to the buffer layer by first mixing the dry anti-sticking material with water and ball-milling it to form an anti-sticking slurry, and then allowing the anti-sticking slurry to soak the entire buffer layer. When the buffer layer is basically dry (that is, no water can be squeezed out of the buffer layer, and the anti-sticking material is embedded in various positions of the buffer layer), quartz sand is spread on the surface of the buffer layer. At this time, because the buffer layer just cannot squeeze out water, it is inevitable that moisture will still remain on the buffer layer. After the buffer layer contacts the fired product, the moisture will be absorbed by the fired product, and the presence of quartz sand will separate the moisture in the buffer layer from the fired product, thereby preventing the fired product from directly absorbing the moisture of the buffer pad and affecting the quality after firing.
[0016] Preferably, as an improvement, the quartz sand laid on the surface of the buffer layer prevents the fired product from directly contacting the buffer layer.
[0017] Preferably, as an improvement, the particle size of the quartz sand is controlled within a range of 60 meshes to 180 meshes.
[0018] Preferably, as an improvement, the thickness of the quartz sand on the buffer layer is 1-2 mm. If the thickness of the quartz sand is thicker, it is easy for the fan to blow the excessively thick quartz sand onto the surface of the fired product during firing in the kiln (to ensure uniform temperature), thereby affecting product quality. If the quartz sand is too thin, it is difficult for the quartz sand to cover the entire upper surface of the refractory wool.
[0019] Preferably, as an improvement, the buffer layer is made of refractory wool.
[0020] Preferably, as an improvement, the refractory wool is immersed in the prepared anti-sticking slurry to achieve embedding of the anti-sticking material in the refractory wool.
[0021] Preferably, as an improvement, the carrier is a cushion bowl, and a buffer layer is placed in the cushion bowl. The thickness of the buffer layer is not less than 5 mm and not more than half of the depth of the cushion bowl, so as to ensure that the buffer pad can play a role, while at the same time preventing the insulator from falling out of the cushion bowl when the insulator tips over due to the excessive thickness of the buffer pad.
[0022] Preferably, as an improvement, the surface of the carrier is also covered with a release layer formed by a release material.
[0023] Preferably, as an improvement, the anti-sticking material includes 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.
[0024] Preferably, as an improvement, the anti-sticking material includes 38-42 parts of industrial alumina, 40-50 parts of quartz powder, 10-15 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.
[0025] Beneficial effect: In the prior art, the anti-sticking material includes high plasticity clay, calcined kaolin and industrial alumina, but the amount of calcined kaolin accounts for about 50%, and whether the calcined kaolin is directly purchased from outside or made by the enterprise itself through calcination process, both methods make the cost of calcined kaolin expensive. The cost of this anti-sticking material is about 5,000 yuan / ton, which is not conducive to the cost reduction and efficiency improvement of the enterprise. In order to reduce the production cost of the enterprise, the inventor only uses industrial alumina and kaolin to configure the anti-sticking material. Although the obtained anti-sticking material can increase the refractory temperature of the anti-sticking material immersed in the refractory cotton, after the anti-sticking material is brushed in the pad bowl as a carrier with anti-sticking slurry, the anti-sticking layer on the surface of the pad bowl has the problem of powder falling and cracking.
[0026] The anti-sticking material of this scheme uses sodium carboxymethyl cellulose, which has never been used before. Sodium carboxymethyl cellulose was originally used in enterprises for glaze slurry preparation. It is very expensive (about 10,000 yuan / ton) and has viscous physical properties. The present invention uses a very small amount of sodium carboxymethyl cellulose. On the basis of considering the cost of use, it utilizes the viscous property of sodium carboxymethyl cellulose. After sodium carboxymethyl cellulose is combined with kaolin, industrial alumina and quartz powder, the water retention of the anti-sticking slurry prepared by adding water to the anti-sticking material can be improved, and the evaporation rate of water in the anti-sticking slurry can be reduced, thereby avoiding the shrinkage stress caused by the excessive shrinkage of the anti-sticking slurry, and then avoiding the generation of cracks.
[0027] In addition, after adding sodium carboxymethyl cellulose, its physical viscosity is utilized to improve the bonding strength between the anti-sticking slurry and the pad bowl as a carrier, which can also reduce the probability of powder falling off.
[0028] In addition, due to its high viscosity, sodium carboxymethyl cellulose can ensure the uniform distribution of various raw materials on the anti-sticking slurry after the various raw materials are evenly stirred. It is also equivalent to the industrial alumina, quartz powder and kaolin contained in the anti-sticking slurry being able to be evenly suspended, thereby avoiding the uneven mixing caused by the sinking of the raw materials under their own density, which ultimately affects the use effect of the anti-sticking slurry.
[0029] In addition, the present invention can avoid the use of calcined kaolin by adding a small amount of sodium carboxymethyl cellulose, and replace it with cheaper quartz sand and kaolin, thereby greatly reducing the cost of the entire anti-sticking material. The cost of the anti-sticking material is reduced from 4,400 yuan / ton under the previous combination of industrial alumina and kaolin to less than 3,000 yuan / ton under the current formula, with a cost reduction of more than 40%, and it can still ensure that there will be no powdering or cracking problems.
[0030] The present invention also provides a method for making an auxiliary tool for insulator firing, comprising the following steps: soaking an elastic buffer layer with anti-sticking slurry, placing the buffer layer on a carrier after the anti-sticking slurry adheres to the buffer layer, and then spreading a layer of quartz sand on the surface of the buffer layer.
[0031] Preferably, as an improvement, before placing the buffer layer on the carrier, the anti-sticking slurry is first brushed on the surface of the carrier, and the buffer layer is placed after the anti-sticking slurry forms an anti-sticking layer on the carrier.
[0032] The present invention also provides a method for using an auxiliary tool for firing an insulator, which requires using the auxiliary tool for firing an insulator, placing a product to be fired on the auxiliary tool for firing an insulator, and then firing the product in a kiln. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic front view and cross-sectional view of an auxiliary tool for firing an insulator according to a first embodiment of the present invention (a porcelain piece to be fired is placed on it, and the porcelain piece is shown in a half-cut structure).
[0034] Figure 2 This is a diagram showing the changes of the bowl used in Example 1 of the present invention before and after the anti-sticking layer is formed.
[0035] Figure 3 It is a main cross-sectional schematic diagram of the relationship between the product to be fired (ceramic part), the anti-sticking layer and the bowl during the anti-sticking slurry test in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] The following is further described in detail through specific implementation methods:
[0037] The reference numerals in the drawings of the specification include: a bowl 10 , an anti-sticking layer 11 , a buffer layer 20 , quartz sand 30 , and a porcelain piece 100 .
[0038] Embodiment 1
[0039] Combination Figure 1 and Figure 2 , an auxiliary tool for firing insulators, comprising a carrier and a buffer pad placed on the carrier, the carrier being a cushion bowl with a U-shaped cross-section, the inner concave surface of the cushion bowl being provided with an anti-sticking layer formed by an anti-sticking material, the buffer pad being placed on the anti-sticking layer, the cushion bowl being made of a porcelain material capable of withstanding the high temperature of a kiln, and in a specific embodiment, the cushion bowl being made of C130 porcelain. The thickness of the anti-sticking layer on the inner cavity surface of the cushion bowl is 0.5-2mm; the thickness of the buffer layer in the cushion bowl is not less than 5mm and not more than half of the depth of the cushion bowl.
[0040] The buffer pad includes an elastic buffer layer, which is made of refractory cotton. The refractory cotton is attached with anti-sticking material in an infiltrated manner. After the buffer pad enters the kiln once, the anti-sticking material and the refractory cotton form a whole to improve the refractory performance of the buffer layer. The anti-sticking material on the buffer pad is the same as the anti-sticking material on the bowl.
[0041] The upper surface of the buffer layer for contacting the fired product is covered with a layer of quartz sand, and the quartz sand is on the buffer layer so that after the fired product is placed on the buffer pad, the fired product will not directly contact the buffer layer.
[0042] The particle size of the quartz sand is controlled at 60 meshes to 180 meshes, the thickness of the quartz sand layer is 1 to 2 mm, and the silicon dioxide content in the quartz sand is higher than 98%.
[0043] This embodiment also provides a method for manufacturing an auxiliary tool for insulator firing, comprising the following steps:
[0044] S1. Making a buffer pad: first prepare an anti-sticking slurry, add water to the anti-sticking slurry and ball-mill it into an anti-sticking slurry with a moisture content of 50%±5% (the ball milling process adopts one-time feeding, and its material: ball: water = 1:2:1.2, and the ball milling fineness is controlled to be 250 mesh (≥0.063mm) and the sieve residue is 2-10%); then press the refractory cotton into the anti-sticking slurry to absorb the anti-sticking slurry, and after the anti-sticking slurry is naturally dried in the shade, place the buffer layer on the pad bowl with the anti-sticking layer.
[0045] The anti-sticking layer on the bowl is formed by brushing the anti-sticking slurry onto the concave surface of the bowl with a brush. After the anti-sticking slurry in the bowl is naturally dried in the shade to form the anti-sticking layer, the buffer pad can be placed.
[0046] S2. Sprinkle a layer of quartz sand particles on the surface of the buffer layer so that the quartz sand particles cover the surface of the refractory wool. The thickness of the quartz sand needs to ensure that the fired porcelain parts will not directly contact the refractory wool during subsequent use.
[0047] The present invention also provides a method for using an auxiliary tool for insulator firing, which is used to place the porcelain piece to be fired into the above-made auxiliary tool for insulator firing, so that the porcelain piece to be fired contacts the quartz sand in the auxiliary tool for insulator firing. After being placed, the auxiliary tool for insulator firing is placed into a kiln for firing.
[0048] When this embodiment is adopted, the large-sized disc-shaped suspension porcelain piece is inverted on the auxiliary tool with its head downward before firing, and the buffer pad on the auxiliary tool directly contacts the fired porcelain piece. In this way, even if the surface of the carrier is uneven, the elastic buffer layer can ensure that the weight of the fired product is evenly transferred to the carrier, thereby ensuring that the porcelain piece of the disc-shaped suspension insulator is evenly stressed during the firing process, greatly reducing or even avoiding the generation of microcracks, and improving the quality and pass rate of the product.
[0049] The refractory material of the buffer layer improves the service life and usage requirements of the buffer pad. The anti-sticking material attached to the buffer layer has excellent refractory properties, which helps to improve the refractory properties of the buffer pad and increase its service life. On the other hand, the buffer pad with anti-sticking material can also reduce adhesion to the burned product and adhesion between the carrier, thereby further improving the service life of the buffer pad.
[0050] In addition, when the buffer pad needs to be replaced, because the buffer pad has anti-stick material and the pad bowl also has an anti-stick layer, the buffer pad is not easy to stick to the pad bowl or to quartz sand or fired porcelain parts. This helps to avoid damage caused by tearing the adhesion position and thus extend the service life, and can also facilitate the replacement of the buffer pad after the elasticity is insufficient.
[0051] Embodiment 2
[0052] Embodiment 2 Based on Embodiment 1, the anti-sticking material is further optimized and designed, as follows:
[0053] The anti-sticking material comprises 30-50 parts of industrial alumina powder, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.
[0054] Industrial alumina powder contains up to 99.5% aluminum oxide.
[0055] The silicon dioxide content in quartz powder is greater than 98%. Quartz powder adopts natural ultra-fine powder material, and its particles ≥0.063mm are only about 3%.
[0056] Kaolin contains about 44% silicon dioxide and about 37.5% aluminum oxide, as well as a small amount of calcium oxide, magnesium oxide, potassium oxide and sodium oxide. It is a clay with a low hydration rate, with an average hydration rate of about 50%. It is also a clay with high plasticity, with an average bonding force of about 20.MPa. Specifically, the kaolin with the chemical composition shown in Table 1 below can be used:
[0057] Table 1 Chemical composition of kaolin
[0058] <![CDATA[SiO2]]> <![CDATA[AI2O3]]> <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> LL % % % % % % % % % 44.0 37.5 0.5 / 0.6 0.4 0.21 0.02 15.0
[0059] Sodium carboxymethyl cellulose is industrial grade sodium carboxymethyl cellulose, which is in the form of fine powder and easy to agglomerate.
[0060] The anti-sticking material of this embodiment has low cost and is not prone to cracking, powdering, and other problems during firing and use.
[0061] The inventors conducted the following multiple formulation tests during the research and development process. The test formulations and test results are shown in Tables 2 and 3 below, respectively:
[0062] Table 2 Different anti-sticking material formulas
[0063] project Industrial alumina (%) Quartz powder(%) Kaolin(%) Sodium carboxymethyl cellulose (%) Cost (Yuan) Recipe 1 88 0 12 0 4457 Recipe 2 60 28 12 0 3291 Recipe 3 10 78 12 0 1208 Recipe 4 20 68 12 0 1625 Recipe 5 50 31.5 18.3 0.2 2891 Recipe 6 40 45 13.8 1.2 2568 Recipe 6.1 38 47 13 2 2558 Recipe 6.2 42 43 14.5 0.5 2586 Recipe 6.3 39 46 13.5 1.5 2554
[0064] Note: The raw material prices in the above formula are calculated on a per ton basis. The highest price of sodium carboxymethyl cellulose is about RMB 10,000 / ton, industrial alumina is about RMB 5,000 / ton, and the prices of quartz powder and kaolin are both within RMB 1,000 / ton.
[0065] The above formulas were uniformly ball-milled in a 50kg ball mill in a pilot laboratory. The ball-milling process adopted a one-time feeding, wherein the material: ball: water = 1:2:1.2, the ball-milling fineness was controlled to be 250 mesh (≥0.063mm), the sieve residue was 2-10%, and the moisture content of the anti-sticking slurry formed after ball-milling was 50%±5%. The anti-sticking slurry was brushed on the bowl in Example 1 as a carrier for testing, and the thickness ensured that the anti-sticking layer formed by the anti-sticking slurry after firing in the kiln was 0.5mm thick. Each time the anti-sticking slurry was fired in the kiln, the product to be fired (such as Figure 3 As shown in the figure, before the bowl brushed with anti-sticking slurry is put into the kiln for the first firing, the product to be fired needs to be placed after the anti-sticking slurry has dried in the shade.
[0066] The cracking rate, powder loss rate and service life after firing in the kiln are recorded for each formula. If the anti-sticking layer of the mat bowl does not crack or powder after the first firing in the kiln, the mat bowl with the anti-sticking layer is put into the kiln again to simulate the firing of electric porcelain. The test is terminated when the anti-sticking layer on the mat bowl cracks or powders. The cracking rate and powder loss rate are the proportion of cracks or powder loss that occur after the first firing in the kiln after the anti-sticking slurry is brushed on the inner surface of the mat bowl. The service life of the mat bowl is defined as: the number of firings in the kiln from the first time the anti-sticking layer is formed on the mat bowl and fired in the kiln to the first time the anti-sticking layer powders or cracks.
[0067] Table 3 Test results of various anti-sticking material formulas
[0068]
[0069] From the above formula 1, it can be seen that the formula 1 is designed to solve the price of the anti-sticking material currently formulated with calcined kaolin, high plasticity clay and industrial alumina. Although the price is lower than the traditional method, the cost reduction is not too much, but the effect is very poor. After the introduction of quartz powder, the particle grading and adhesion of formula 2 are better than those of formula 1, and the cracking rate and powder loss rate are significantly improved under the physical and chemical action between the raw materials, especially the cracking rate is reduced by 10%, indicating that the addition of quartz powder helps to improve the formula, but the effect still needs to be improved.
[0070] After trying formula 3 and increasing the amount of quartz powder, the sieve residue was reduced to 1%. This is because quartz powder is very fine, with a particle size of 220-600 mesh, and can be directly sieved. However, the effect is worse in terms of cracking rate compared to formula 1, which shows that quartz powder should not be added too much.
[0071] Compared with Formula 1, Formula 4 has more advantages in terms of cracking rate and powder loss rate. The most prominent advantage is that the cost is reduced to more than 1,000 yuan / ton, which is equivalent to a significant reduction in cost while achieving basically the same or even slightly better results as the expensive Formula 1. However, this is far from enough for the firing of porcelain for large-sized disc suspension insulators with high mechanical load requirements.
[0072] Under Formula 5, after readjusting the dosage of industrial alumina, quartz powder, and kaolin, and adding 0.2% sodium carboxymethyl cellulose, the cracking rate was greatly controlled, and the cracking rate was reduced from 70-80% in Formulas 1-4 to 12%, and the powder loss rate was also reduced a lot. The cost was also reduced from more than 4,000 / ton in Formula 1 to more than 2,000 / ton, and the service life of the anti-sticking layer formed by the anti-sticking slurry brushed on the bowl was also extended from the original 1 time to 2 times.
[0073] Based on the great progress of Formula 5, a small adjustment was made to obtain Formula 6. From the test results of Formula 6, it can be seen that after increasing the amount of sodium carboxymethyl cellulose and quartz powder on the basis of Formula 5 and reducing the amount of industrial alumina and kaolin, the cracking rate and powder loss rate were further reduced to 1%. The cost is also more than 2,000 yuan / ton.
[0074] It can be seen that sodium carboxymethyl cellulose plays a very critical role in the anti-sticking material. Through analysis, it is found that the anti-sticking slurry with sodium carboxymethyl cellulose added has a slower evaporation rate of water, which means that the water retention is improved and the cracking problem caused by excessive shrinkage after subsequent firing is reduced; at the same time, the adhesion between the anti-sticking material and the bowl is also improved. From the test, it can be seen that the powder loss rate at the transition point between the inner wall of the bowl and the arc at the top of the inner cavity, where powder loss is prone to occur, is greatly reduced, which shows that its bonding with the bowl is also improved. In addition, the viscosity of sodium carboxymethyl cellulose allows the various components of the anti-sticking slurry that is evenly milled to be evenly suspended, which helps to improve the quality of the anti-sticking layer and the thickness uniformity of the anti-sticking layer.
[0075] In addition, the inventors also tested the addition of more sodium carboxymethyl cellulose to the anti-sticking material. For example, on the basis of Formula 6, 0.5% and 1% of sodium carboxymethyl cellulose were added to form an anti-sticking slurry. It was found that the anti-sticking slurry can still ensure a very low cracking rate and powder loss rate, and the service life can reach 4 times. The only inappropriate thing is that the anti-sticking slurry is more viscous, and it is more difficult for workers to brush the anti-sticking slurry, which affects efficiency.
[0076] In addition, in order to ensure process stability, Formula 6 was fine-tuned to obtain Formula 6.1, Formula 6.2 and Formula 6.3. The fine-tuned formulas can still meet extremely low cracking rate and powder loss rate, and the service life can reach 4 times. Compared with the situation where the bowl needs to be brushed with anti-sticking slurry every time it is fired twice or once in the kiln, the present invention greatly reduces the number of times the anti-sticking slurry is brushed, which helps to reduce labor intensity and cost.
[0077] In summary, the anti-sticking material of this embodiment not only has superior performance, but also significantly reduces the cost of raw materials, and its preparation method is simple and convenient. In addition, the anti-sticking material has a wide range of applications, and is suitable for forming an anti-sticking layer in the inner cavity of a bowl, and can also be used to embed an anti-sticking material in a cushion pad, showing excellent versatility and practicality.
[0078] Embodiment 3
[0079] Implementation three further optimizes the design of the buffer pad based on implementation example one, with specific requirements that the mass proportion of quartz sand, refractory wool and anti-sticking material on the buffer pad under dry material is quartz sand accounting for 10-20%, refractory wool accounting for 40-60%, and anti-sticking material accounting for 25-45%.
[0080] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. An auxiliary tool for insulator firing, characterized in that: The invention comprises a carrier and a buffer pad placed on the carrier, wherein the buffer pad comprises an elastic buffer layer made of a refractory material, and the buffer layer is embedded with an anti-sticking material.
2. The auxiliary tool for insulator firing according to claim 1, characterized in that: The surface of the buffer layer for contacting the sintered product is paved with a layer of quartz sand.
3. The auxiliary tool for insulator firing according to claim 2, characterized in that: The quartz sand laid on the surface of the buffer layer prevents the fired product from directly contacting the buffer layer.
4. The auxiliary tool for insulator firing according to claim 3, characterized in that: The buffer layer is made of fire-resistant cotton.
5. The auxiliary tool for insulator firing according to claim 1, characterized in that: The carrier is a cushion bowl, and the buffer layer is placed in the cushion bowl. The thickness of the buffer layer is not less than 5 mm and not more than half of the depth of the cushion bowl.
6. The auxiliary tool for insulator firing according to claim 1, characterized in that: The surface of the carrier is also covered with an anti-sticking layer formed by an anti-sticking material.
7. An auxiliary tool for insulator sintering according to any one of claims 1 to 6, characterized in that: The anti-sticking material comprises 30-50 parts of industrial alumina, 35-55 parts of quartz powder, 10-30 parts of kaolin and 0.5-2 parts of sodium carboxymethyl cellulose.
8. A method for manufacturing an auxiliary tool for insulator firing, characterized in that: The method comprises the following steps: soaking the elastic buffer layer with anti-sticking slurry, placing the buffer layer on a carrier after the anti-sticking slurry is attached to the buffer layer, and then spreading a layer of quartz sand on the surface of the buffer layer.
9. The method for manufacturing an auxiliary tool for insulator firing according to claim 8, characterized in that: Before placing the buffer layer on the carrier, first brush the anti-sticking slurry on the surface of the carrier, and then place the buffer layer after the anti-sticking slurry forms an anti-sticking layer on the carrier.
10. A method for using an auxiliary tool for insulator firing, characterized in that: It is necessary to use the auxiliary tool for firing an insulator according to any one of claims 1 to 6, place the product to be fired on the auxiliary tool for firing an insulator and then put it into the kiln for firing.
Citation Information
Patent Citations
Special rod-shaped adhesive for loading and sintering of electrical porcelain
CN113880556A